Influence of Non-metallic Inclusions on Corrosive Properties of Polar Steel - Li, Ming; Wu, Huajie; Sun, Yanhui (Frontiers in Materials, 2021)
Polar steel requires excellent toughness and corrosion resistancefor breaking icy surfaces in low-temperature seawater environments. In this study, theeffect of inclusions on the corrosion resistance of polar steel is examined. In experiments, composition and morphology of the inclusions in steel were controlled by different deoxidation methods during steel refining. The morphology and composition of the corrosion-resistant active inclusions were analysedusingscanning electron microscopy andenergy dispersive spectroscopy.The corrosive resistance of polar steelwas determined by measuring the saturation current density of the anodic dissolution of steel in a corrosive medium via an electrochemical method. The corrosive resistanceunder simulating seawater wasalso investigated in laboratory condition. It is found that as the ratio of Al/Mg approaches the stoichiometric composition of the spinel (2.3–2.5), the inclusions becomes less active; as the ratio further increases, the corrosion-resistant activity increases due to the formation of MgAl2O4·CaO complexes, leading to an increase in local stress around the inclusions.If steel is deoxidized with Zr–Ti, small Zr–Ti complex oxides form in the steel, providing nucleation particles for the precipitation of spheroidised and uniformly distributed MnS.Therefore, steel deoxidized with Zr–Ti has better seawater corrosion resistance than Al-deoxidized steel.